Multiple hierarchical dynamic interactions enabled a robust, stretchable and room temperature self-healing elastomer. Issue 17 (12th April 2023) - Fan, Jianfeng; Zhou, Xinqin; Chen, Yukun
Abstract : The reported strategy of control of elastomers' mechanical hierarchy of energy-dissipating modes provides practical experience for the design of efficient self-healing elastomers with robust and stretchable mechanical properties. Abstract : It is challenging to simultaneously improve the self-healing ability and toughness of thermoplastic polydimethylsiloxane (PDMS) elastomers due to their mutually exclusive dependence on molecular structures. In this work, abundant metal–ligand coordination cross-links were embedded in a hydrogen-bonded network, toward synchronously realizing efficient self-healing at room temperature and robust and stretchable mechanical properties. The hydrogen bonds endow the elastomer with excellent stretchability via multiple mechanisms of energy dissipation, while the metal–ligand coordination complexes/clusters significantly improve the robustness and elasticity of the elastomer due to their reinforcement effect. The integration of strong coordination complexes and weak hydrogen bonds can optimize the mechanical properties of the elastomer, simultaneously providing high tensile strength (0.8 MPa), high stretchability (1326%), and moderate fracture toughness (7.1 MJ m −3 ). Additionally, the robust and stretchable PDMS elastomer was also able to spontaneously self-heal without the input of external energy with the highest healing efficiency of 100%. This strategy of control of the elastomer's mechanical hierarchy of energy-dissipating modes provides practical experience for the design of efficient self-healing elastomers with robust and stretchable mechanical properties.